PEMBINAAN DAN PENGENDALIAN KAWASAN HUTAN DI PROVINSI RIAU - M. Nowaldi Rama; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the governance guidance and control of production forests in Riau Province. As for the background of this study is a) the rampant conversion of forest area of ​​protected forest areas / nature / reserves into production forest plantation area or other uses (APL), b) the emergence of catastrophic fires and smoke haze as a result of the shift in the status area the forests and c) the increase of illegal logging and illegal practice of trading both forest products and forest areas. Associated with that background, the underlying idea of ​​this study on the theoretical framework of authority (authority). For tracking information and data needed, this study used a qualitative approach to data collection techniques interviews and documentation of the data of both primary and secondary. Further analysis of the data conducted a qualitative descriptive describes the condition of empirical research on the issue.This study finally shows that; First, the guidance and control of forest governance in the province of Riau production refers to the legislation that exists. Therefore, in an effort to provide guidance and control of forest governance of production, Riau Forestry Service planning for forest management of production, development and control of the business of production of forestry to encourage the restructuring and rationalization of the forestry industry, make a plan and the realization of the raw material industry ( in the province / out of province / import), draw up a framework for the sector which includes ecological, social, economic and institutional as well as to safeguard forest areas.Second, are factors inhibiting the development and governance pengedalian production forests in Riau Province, namely the legality of the country's forests, licensing control problems, structural problems and institutional capacity as well as control of information by the private sector problem.Keywords: Governance, Authority, Forest Production